Model Predictive Direct Current Control (MPDCC) for Grid Connected Application - Aida, Azuwien; Goh, H.H.; Lee, S.S.; Sim, S.Y. (International Journal of Integrated Engineering, 2019)
This paper deals with the design and simulation of Dual Active Bridge Multilevel Inverter (DABMI) based Model Predictive Direct Current Control (MPDCC) for grid connected application. To achieve multilevel output voltage waveforms, the second inverter will be supply with half of the dc-link voltage. Model predictive direct current control used to control the grid current component in order to achieve minimum grid current error. Modulation is unnecessary in this system because the switching pattern is produce by the possible switching that determined by the proposed MPDCC. The voltage vector which minimizes the cost function will be selected and applied to track the reference current. The performance of the proposed MPDCC is observe and implement by MATLAB/Simulink Software.